The impact of post-dilatation on periprocedural outcomes during carotid artery stenting: A single-center experience. (November 2019) - Besli, Feyzullah; Gungoren, Fatih; Kocaturk, Ozcan; Tanriverdi, Zulkif; Tascanov, Mustafa Begenc
Abstract: Background and aims: Carotid artery stenting (CAS) is an accepted treatment modality for carotid artery disease. However, CAS is associated with periprocedural embolic events, and the effect of balloon post-dilatation has not been sufficiently investigated in large studies. We assessed the effect of post-dilatation on periprocedural outcomes during CAS. Methods: The study included 128 patients who underwent CAS. The patients were divided into groups according to whether post-dilatation was (post-dilatation [+], group 1) or was not (post dilatation [−], group 2) performed after stent deployment. Major adverse events were defined as death, minor or major stroke, and transient ischemic attack at 30 days. Silent ischemia was assessed using diffusion-weighted magnetic resonance imaging. Results: No significant between-group differences were found in baseline characteristics, comorbid diseases, or lesion characteristics. The degree of stenosis and procedure duration was greater in group 1 than in group 2. The rate of major adverse events at 30 days was similar between the two groups (5.1% vs. 4.3%, p = 0.844). The silent ischemia rate and number of high-intensity signals were higher in group 1 than in group 2 (45.8% vs. 26.1%, p = 0.020 and 1.01 [1.2] vs. 0.42 [0.79], p = 0.002). Multivariate analysis revealed that post-dilatation was associated with a 2.4-fold increase in silent ischemia (95% confidence interval: 1.15–5.20, p = 0.020). Conclusions: Although post-dilatation was not associated with an increase in major adverse events, it significantly increased the incidence of periprocedural silent ischemia. Therefore, post-dilation should be performed only in cases with severe residual stenosis after CAS. Graphical abstract: Image 1 Highlights: Carotid artery stenting is well known therapy modality in setting of carotid artery disease. Post-dilatation is not associated major adverse events at 30 days. Post-dilatation independent predictor of silent cerebral ischemia in patients undergoing CAS. Post-dilatation should be limited only in cases with severe residual stenosis after stenting during CAS as possible as.